Nanostructure characterization of carbide-derived carbons by morphological analysis of transmission electron microscopy images combined with physisorption and Raman spectroscopy - Oschatz, Martin; Pre, Pascaline; Doerfler, Susanne; Nickel, Winfried; Beaunier, Patricia; Rouzaud, Jean-Noel; Fischer, Cathleen; Brunner, Eike; Kaskel, Stefan (Carbon, 2016)
A novel image processing method based on mathematical morphology is applied in order to characterize the nanostructure of carbide-derived carbons (CDCs) observed using high resolution transmission electron microscopy (HRTEM). The analysis provides information about the shape and disordered arrangement of the defective polyaromatic units forming the CDC nanostructure. Individual fringes, basic structural units, and continuous domains are analysed. Hierarchical polycarbosilane-based CDCs obtained at different pyrolysis/chlorination temperatures are investigated. The information collected is interpreted with respect to the different synthesis conditions. This analysis is supported by Raman spectroscopy measurements and porosity evaluation with nitrogen (-196 °C) and carbon dioxide (0 °C) physisorption. The CDCs show only minor differences in the carbon nanostructures. The HRTEM image analysis is sensitive enough to illuminate the slight variations. An increase in carbon ordering at higher synthesis temperature and a rather folded structure with higher tortuosity of the fringes with increasing micropore volume is observed. These findings are complementary to the data obtained from nitrogen and carbon dioxide physisorption experiments as well as from Raman spectroscopy, showing a less defective microstructure of the CDCs prepared at higher pyrolysis/chlorination temperatures. The results also prove the precise control over the nanostructure of CDCs provided by the synthesis temperature.
CRIS-Team Scopus Importer:2023-03-20